iMITEdb: the genome-wide landscape of miniature inverted-repeat transposable elements in insects - Han, Min-Jin (Database (Oxford), 2016)
Miniature inverted-repeat transposable elements (MITEs) have attracted much attention due to their widespread occurrence and high copy numbers in eukaryotic genomes. However, the systematic knowledge about MITEs in insects and other animals is still lacking. In this study, we identified 6012 MITE families from 98 insect species genomes. Comparison of these MITEs with known MITEs in the NCBI non-redundant database and Repbase showed that 5701(∼95%) of 6012 MITE families are novel. The abundance of MITEs varies drastically among different insect species, and significantly correlates with genome size. In general, larger genomes contain more MITEs than small genomes. Furthermore, all identified MITEs were included in a newly constructed database (iMITEdb) (http://gene.cqu.edu.cn/iMITEdb/), which has functions such as browse, search, BLAST and download. Overall, our results not only provide insight on insect MITEs but will also improve assembly and annotation of insect genomes. More importantly, the results presented in this study will promote studies of MITEs function, evolution and application in insects. Database URL: http://gene.cqu.edu.cn/iMITEdb/